From traditional to digital: The role of smart streaming television in shaping media consumption habits of rural elderly in China - MENGHUAN WU; NURUL HIJJA MAZLAN; NUR NASLIZA ARINA BINTI MOHAMAD NASIR; WARDATUL HAYAT ADNAN (Environment and Social Psychology, 2025)
Smart streaming television represents a potential bridge between traditional and digital media for elderly populations, yet its adoption and impact remain understudied in rural contexts. This mixed-methods study investigated smart TV adoption patterns and media consumption changes among 342 rural elderly participants in Shandong Province, China. Quantitative surveys assessed technology ownership, digital literacy, and usage patterns, while qualitative interviews with 48 participants explored adoption experiences and barriers.Results revealed 63.5% smart TV ownership with varied usage patterns: 49.1% actively used digital features, 14.4% used devices as traditional TV replacements, and 5.3% owned but never activated smart TVs, indicating significant adoption-usage gaps. Structural equation modeling identified perceived usefulness (β=0.52), social influence (β=0.43), and family support (β=0.38) as primary adoption facilitators. Major barriers included technical complexity (76.8% of non-adopters), limited digital literacy (basic navigation proficiency ranging from 64% to 24% across age groups), economic constraints, and infrastructure limitations affecting 43.2% of villages. Among active users, media consumption transformed significantly. Daily viewing increased from 4.2 to 6.0 hours, active content selection rose from 12.5% to 78.6%, and family co-viewing grew by 58.0%. Health program viewership increased 157.6%, while traditional opera consumption rose 117.5%. However, traditional viewing habits persisted alongside digital adoption, suggesting complementary rather than replacement relationships. These findings indicate that smart TV adoption among rural elderly involves complex negotiations between technological opportunities and contextual constraints. Successful integration requires user-centered design, sustained family support, infrastructure development, and content curation aligned with elderly users’ cultural preferences. The study contributes to understanding digital inclusion challenges and opportunities for aging populations in rapidly digitalizing societies.